The Glorious Political Role of Muslim Women in Freedom Movement of Pakistan; (Historical Study) : "تحریک آزادی پاکستان میں مسلمان خواتین کامثالی سیاسی کردار تاریخ کے آئینے میں" ایک تحقیقی جائزہ - Lalwani, Naila Naz; Bibi, Naseeba; Adnan, Abdul Sattar (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
The role of Muslim women in freedom moment is one of the important chapters of history of Pakistan but it is a salient chapter of the history of Indian Muslims. The down fall of Muslim’s rule in India bitterly damaged the Muslims in every walk of life. In early twentieth century Muslims decided to start a freedom against the colonial masters. With men the Muslim’s women also participated in this moment with total commitment and played a splendid role. Due their efforts Muslim League became popular in Muslims majority areas. These brave women also changed the political situation against Khizair Tiwana during the civil disobedient moment. Fatima swing Muslim League flag on civil secretariate and put of Union Jack. This paper highlights the political contribution of Muslim women during freedom moment of Pakistan.